Cultural adaptation and reliability of the General Comfort Questionnaire for chronic renal patients in Brazil - Geórgia Alcântara Alencar Melo; Renan Alves Silva; Francisco Gilberto Fernandes Pereira; Joselany Áfio Caetano (Universidade de São Paulo, 2017)
ABSTRACT Objective: to make the cultural adaptation and evaluate the reliability of the Brazilian version of the General Comfort Questionnaire for chronic hemodialytic renal patients. Method: methodological study with the following steps: translation; consensus among judges; back-translation; validation of equivalence (semantic, idiomatic, experimental and conceptual) by 12 judges; and pre-test with 80 chronic renal patients on hemodialysis. Reliability was checked through measures of internal consistency (Cronbach's alpha). Results: the overall consensus of the instrument had 94.3% of equivalence. Twenty-one items of the instrument were modified. Of these, only two needed semantic and idiomatic changes. The other 19 underwent few modifications, such as reversing words in the sentence and replacing some corresponding synonym terms. The Cronbach's alpha was 0.80, indicating optimal internal consistency. In the application, the total score ranged from 116 to 172 points (M = 151.66; SD = ± 12.60). Conclusion: the validation of the Portuguese version of the instrument represents one additional resource to be made available to nephrologist nurses; it will aid in directing the decision-making so that the nursing interventions be performed according to the level of comfort and domain, either physical, socio-cultural, environmental or psycho-spiritual. The tool was named in Portuguese: General Comfort Questionnaire - Brazilian version.